Analysis of the Use of Nomina Clauses in the Newspaper Detik News - Simbolon, Khusnul Tri Juliani; Amri, Yusni Khairul (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2024)
This research aims to describe the types of noun clauses found in the Detik newspaper on 12 May 2024. Noun clauses, active verbs, and prepositions are types of clauses that are classified according to the type of filler in the predicate function. Listening and taking notes were the data collection methods used. Qualitative descriptive analysis was used to analyze research data. Based on the predicate function of noun clauses, the researchers found that there were 3 noun clause data in the detik news newspaper. However, not only the noun clauses in this newspaper contain Adjectival Clauses, Independent Equative Clauses, Negative Equative Clauses, Main Clauses, Subordinate Clauses, Relative Clauses, Independent Verbal Clauses, and Verbal Clauses.